VD_FINDINFO Jug / 2017 / 386 vom 19. Juni 2017 - VD Tribunal cantonal (2017)
DÉCISION D'IRRECEVABILITÉ, QUALITÉ POUR RECOURIR, LÉSÉ, PLAIGNANT, MASSE EN FAILLITE, SUBROGATION | 115 al. 1 CPP (CH), 121 al. 2 CPP (CH), 382 al. 2 CPP (CH), 403 al. 1 let. a CPP (CH), 403 al. 2 CPP (CH)